2012
DOI: 10.1088/0957-4484/23/27/275101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gadolinium oxide nanoparticles on the oxidative burst from human neutrophil granulocytes

Abstract: We have previously shown that gadolinium oxide (Gd(2)O(3)) nanoparticles are promising candidates to be used as contrast agents in magnetic resonance (MR) imaging applications. In this study, these nanoparticles were investigated in a cellular system, as possible probes for visualization and targeting intended for bioimaging applications. We evaluated the impact of the presence of Gd(2)O(3) nanoparticles on the production of reactive oxygen species (ROS) from human neutrophils, by means of luminol-dependent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Under physiological conditions this enzyme complex is latent in phagocytic cells. However, nanomaterials can activate the inflammatory cells inducing a respiratory burst in the absence of bacteria (Abrikossova et al, 2012, Tulinska et al, 2013). NADPH oxidase is abundant in “professional” phagocytes but this protein is also present in non inflammatory cells where it contributes to cell signaling.…”
Section: 2 Hierarchical Oxidative Stress Modelmentioning
confidence: 99%
“…Under physiological conditions this enzyme complex is latent in phagocytic cells. However, nanomaterials can activate the inflammatory cells inducing a respiratory burst in the absence of bacteria (Abrikossova et al, 2012, Tulinska et al, 2013). NADPH oxidase is abundant in “professional” phagocytes but this protein is also present in non inflammatory cells where it contributes to cell signaling.…”
Section: 2 Hierarchical Oxidative Stress Modelmentioning
confidence: 99%
“…Nevertheless, the safety of these nanoparticles, as well as their effects in host defense system, remains unestablished. Particularly, direct activation of polymorphonuclear neutrophil cells (PMNs), key player cells in inflammation, by different AgNPs is poorly documented, despite the fact that accumulating data indicate that PMN biology could be altered by different kinds of NPs [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the literature dealing with the direct effects of NP on PMN is not well documented, even if our group (Babin et al 2013;Goncalves and Girard 2014;Goncalves et al 2010;Poirier et al 2014) and others (Abrikossova et al 2012;Bartneck et al 2010;Chekanov et al 2013;Couto et al 2014;Moeller et al 2012;Papatheofanis and Barmada 1991) reported that different kinds of NP can activate human PMN, leading to distinct modulatory activities on functional responses including reactive oxygen species (ROS) production, cytokine formation, apoptosis and degranulation. Among these studies, it was previously reported that silver NP (AgNP) with a diameter of 20 nm (AgNP 20 ) induced human neutrophil apoptosis and inhibited de novo protein synthesis (Poirier et al 2014).…”
Section: Introductionmentioning
confidence: 97%